PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING MATERI EKOSISTEM TERHADAP KETERAMPILAN PROSES SAINS PESERTA DIDIK KELAS V SDN PILANG 1 SIDOARJO - Alya Rohani Su’udah; Arie Widya Murni (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2022)
This research is motivated by the problems of learning science in schools which are generally carried out using the teacher centered learning model, which means that only the teacher is active in learning. So this study aims to determine the effect of problem-based learning models with science process skills on students' active learning. This research is a quantitative study using the pre-experimental method type one group pretest posttest. The population and sample in this study were 30 students in class VA at SD Pilang 1, Wonoayu District, Sidoarjo Regency. In this study, researchers used the pretest as the first benchmark before being given treatment by researchers to get an average result of 52.01. Then the second benchmark uses the posttest after being given treatment by the researcher to get an average result of 87.15. In this study, the tcount was 24.0792 and the ttable was 2.04522964. The conclusion of the research results shows that there is a significant influence between the use of problem based learning models on science process skills